Milking Practices Followed by Dairy Farmers of Kheda and Panchmahal Districts of Middle Gujarat - Divekar, B. S.; Trivedi , M. M. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was undertaken in Kheda and Panchmahal districts of middle Gujarat to know the existing milking management practices followed by the dairy farmers. The study was conducted in randomly selected four talukas each from Kheda and Panchmahal districts. From each taluka five villages and from each village five respondents were randomly selected. Thus, total 200 respondents were included in the study. Data revealed that all the respondents milked their animals twice a day and majority (79.50 %) of them were using knuckling method of hand milking. Further, more than two third of respondents were practicing wet hand milking. Bathing and/or grooming of animals before milking, washing of teats/udder prior to milking and washing of the hands before milking were practiced by 76.50, 81.00 and 74.50 % of the dairy farmers, respectively. Farmers of Panchmahal district neither followed post-milking teats’ dipping nor carried out mastitis detection tests. However, in Kheda district some dairy farmers practiced post-milking teats’ dipping (6.50 %) and mastitis detection tests (3.50 %).